Pediatric hospital demand in the COVID-19 pandemic - Rizo Patron, Emiliana (2020)
The COVID-19 pandemic in Perú is causing an unusual pressure in our sanitarian and critic care resources. As the pandemics have progressed in the population, an increasing of several cases and intensive care units (ICU) demand will be expected, because of that, the hospitals capacities would be exceeded in a short place. Despite the low severity of COVID-19 cases in children, we expect that the projected number of pediatric cases could overwhelm the available pediatric capacity. Under a 25% cumulative infection rate scenario, there would be approximately 891 critically ill children requiring ICU admission. We propose several strategies to handle the concerns about shortfalls in our ability to provide pediatric ventilation and critical care support during the epidemic in Perú.